2023
DOI: 10.3390/microorganisms11092234
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspectives on Food-Based Natural Antimicrobials: A Review of Recent Findings Published since 2020

Taner Sar,
Pelin Kiraz,
Vjola Braho
et al.

Abstract: Various fruit and vegetable wastes, particularly peels, seeds, pulp, and unprocessed residues from the food industry, are abundant sources of antioxidants and essential antimicrobial agents. These valuable bioactive compounds recovered from the food industry have a great application in food, agriculture, medicine, and pharmacology. Food-derived natural antimicrobials offer advantages such as diminishing microbial loads and prolonging the shelf life of food products particularly prone to microbial spoilage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…Ajose et al 2023, have recently reviewed ethnoveterinary medicinal plants and ethnoveterinary medicinal products utilised in dairy and livestock farming to combat mastitis, with the most prominent plants as Becium obovatum , Malva parviflora , Brucea antidysenterica , Acorus calamus L., Triticum sp, Arachis hypogeam , Peganum harmala , Citrus limon , Withania somnifera and others [ 8 ]. Among plant extracts, Sorghum phenol extract [ 5 ], sweet orange peel ( Citrus sinensis ), pomegranate ( Punica granatum ) [ 22 , 23 ], indian screw tree ( Helicteres isora ) [ 24 ], lemon balm ( Melissa officinalis ), a specie of laurel wood ( Knema retusa ) [ 25 ] and olive [ 13 ] extracts demonstrated strong antimicrobial activity against different S. aureus strains including other BM-associated pathogens. After in vitro disc diffusion assays from recent studies, the authors have reported the inhibitory zones against S. aureus significant average zones ranging from 22 to 31 mm [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ajose et al 2023, have recently reviewed ethnoveterinary medicinal plants and ethnoveterinary medicinal products utilised in dairy and livestock farming to combat mastitis, with the most prominent plants as Becium obovatum , Malva parviflora , Brucea antidysenterica , Acorus calamus L., Triticum sp, Arachis hypogeam , Peganum harmala , Citrus limon , Withania somnifera and others [ 8 ]. Among plant extracts, Sorghum phenol extract [ 5 ], sweet orange peel ( Citrus sinensis ), pomegranate ( Punica granatum ) [ 22 , 23 ], indian screw tree ( Helicteres isora ) [ 24 ], lemon balm ( Melissa officinalis ), a specie of laurel wood ( Knema retusa ) [ 25 ] and olive [ 13 ] extracts demonstrated strong antimicrobial activity against different S. aureus strains including other BM-associated pathogens. After in vitro disc diffusion assays from recent studies, the authors have reported the inhibitory zones against S. aureus significant average zones ranging from 22 to 31 mm [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%